Corporate Governance Quality : Trends and Real Effects - Ueda, Kenichi (IMF Working Papers; Working Paper ;, 2006)
This paper constructs a composite index of corporate governance quality, documents its evolution from 1994 through 2003 in selected emerging and developed economies, and assesses its impact on aggregate and corporate growth and productivity. Our investigation yields three main findings. First, corporate governance quality in most countries has overall improved, although to varying degrees and with a few notable exceptions. Second, the data exhibit cross-country convergence in corporate governance quality with countries that score poorly initially catching up with countries with high corporate governance scores. Third, the impact of improvements in corporate governance quality on traditional measures of real economic activity-GDP growth, productivity growth, and the ratio of investment to GDP- is positive, significant, and quantitatively relevant, and the growth effect is particularly pronounced for industries that are most dependent on external finance.